Investigation of the atmospheric gravity wave impact on the ionospheric dynamo region with the EISCAT incoherent scatter radar - Günzkofer, Florian Ludwig; Stober, Gunter; Pokhotelov, Dimitry; Borries, Claudia (2024)
At high-latitudes, the strong field-aligned ionospheric currents are closed at approximately 100 - 130 km altitude due to the maxima of Pedersen and Hall conductivity. Atmosphere-ionosphere coupling processes at these altitudes can therefore have a significant impact on the ionospheric variability. Incoherent Scatter Radars (ISRs) are capable to cover the entire altitude range of the ionospheric dynamo region and provide measurements of multiple plasma parameters. We demonstrate the application of ISR measurements to study atmosphere-ionosphere coupling processes, e.g. the impact of atmospheric gravity waves on the ionosphere. In combination with the Nordic Meteor Radar Cluster, EISCAT ISR measurements provide 3D observations of gravity wave parameters which allows to infer neutral wind velocities along the wave propagation direction. Another important coupling process is the dissipation of ionospheric currents which is a major source of thermal energy to both the ionosphere and the neutral atmosphere. We present altitude-resolved profiles of this Joule heating from a large number of EISCAT ISR beam-swinging measurements. Since ionosphere models often underestimate the actual Joule heating rate, the TIE-GCM model applies an empirical scaling of the Joule heating rate by a factor 1.5. We show measurement-model comparisons which suggest that it might be useful to vary this scaling with respect to geomagnetic activity, magnetic local time and the applied plasma convection model. Finally, the key parameter for all atmosphere-ionosphere coupling processes is the ion-neutral collision frequency. We demonstrate the difference spectrum method which allows to infer collision frequency profiles from simultaneous ISR measurements at two different radar frequencies. This method is based on standard ISR analysis software and could increase the very small number of direct collision frequency measurements in the ionosphere.